FAKTA KASUS KEKERASAN DALAM RUMAH TANGGA (KDRT) DI DEPOK SUAMI DAN ISTRI SAMA-SAMA JADI TERSANGKA TAPI HANYA ISTRI YANG DITAHAN ANALISIS WACANA KRITIS MODEL SARA MILLS - Nurul Hasan; Agus Hamdani (Indonesian language and literature education program Majapahit Islamic University, 2023)
Domestic violence refers to various physical, emotional, psychological, or sexual actions carried out by one family member against another within the household or domestic relationship. The author employs a descriptive analysis method in this research. The data source for this study is an article titled